2018
DOI: 10.1002/cam4.1343
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity across the lifespan and liver cancer incidence in the NIH‐AARP Diet and Health Study cohort

Abstract: While liver cancer rates in the United States are increasing, 5‐year survival is only 17.6%, underscoring the importance of prevention. Physical activity has been associated with lower risk of developing liver cancer, but most studies assess physical activity only at a single point in time, often in midlife. We utilized physical activity data from 296,661 men and women in the NIH‐AARP Diet and Health Study cohort to test whether physical activity patterns over the life course could elucidate the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…Among the 22 reviewed publications, studies (with possible overlap) were excluded from the primary meta-analysis on physical activity and liver cancer if the exposure variable was not physical activity (n = 6) [32][33][34][35][36][37], or if the outcome was not liver cancer (n = 1) [19]; or the effect estimates for physical activity were not shown (n= 4) [32,33,37,38]. Additionally, studies were excluded, if the study design was not prospective (n=5) [39][40][41][42][43], or if the article had a shorter follow-up or fewer events than another publication from the same study (n=5) [16,37,[44][45][46]. in Europe, and four in Asian countries.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Among the 22 reviewed publications, studies (with possible overlap) were excluded from the primary meta-analysis on physical activity and liver cancer if the exposure variable was not physical activity (n = 6) [32][33][34][35][36][37], or if the outcome was not liver cancer (n = 1) [19]; or the effect estimates for physical activity were not shown (n= 4) [32,33,37,38]. Additionally, studies were excluded, if the study design was not prospective (n=5) [39][40][41][42][43], or if the article had a shorter follow-up or fewer events than another publication from the same study (n=5) [16,37,[44][45][46]. in Europe, and four in Asian countries.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…We performed sensitivity analyses to address potential selection bias, differences in case ascertainment between centers, and additional unobserved confounding. Although HBV and HCV are considered among the strongest risk factors for HCC [3], previous studies [8][9][10][11][12][13]37] were unable to adjust for HBV and HCV. In the EPIC nested case control study the size and direction of the effect size for the association of physical activity and HCC was similar to that of the entire EPIC cohort; however, it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity and anthropometric measures were assessed only once at baseline. [9] revealed that consistent participation in physical activity throughout the life course might be needed to reduce the risk of liver cancer incidence. We performed mediation analysis for indirect effects acting through general and central obesity, but we were unable to study trajectories of physical activity and body weight that could help to better separate the role of obesity as a confounder and mediator of the association of physical activity and risk of hepatobiliary cancer [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The European Prospective Investigation into Cancer and Nutrition (EPIC) study recruited 477,206 patients from all over Europe and demonstrated an inverse association between total fat intake (per 10 g/day hazards ratio [HR] = 0.80; 95% CI = 0.65–0.99), while there was no association with meat intake [ 69 ]. The NIH-AARP study, which prospectively enrolled almost 500,000 men and women, reported an increased risk for HCC associated with intake of saturated fat and red meat [ 70 ]. A prospective, randomised, controlled trial in postmenopausal women could not show any beneficial effect of a low-fat diet on the incidence of liver cancer (HR = 0.95, 95% CI = 0.89–1.01; p = 0.10) [ 71 ].…”
Section: Risk Factorsmentioning
confidence: 99%